Emotional and behavioral resilience among children with perinatally acquired HIV in Thailand and Cambodia - Kathleen M. Malee (2019)
OBJECTIVES: Psychosocial challenges associated with perinatally acquired HIV (PHIV) infection are well known, yet many children infected with HIV since birth demonstrate positive outcomes, referred to as resilience. The purpose of this study was to evaluate emotional-behavioral development and identify salient predictors of resilience among long-term survivors of PHIV. DESIGN: Prospective investigation of children with PHIV compared with demographically similar perinatally HIV-exposed but uninfected (PHEU) and HIV-unexposed, uninfected (HUU) children, all from Thailand and Cambodia. METHODS: The Child Behavior Checklist (CBCL; parent version) was administered at baseline and annual follow-up visits (median follow-up of 3 years) to children age 6-14. Resilience was defined as consistent CBCL scores on the Internalizing, Externalizing or Total Problem T scales within normative ranges (T-scores <60) at every time point. Generalized estimating equations examined CBCL scores over time and logistic models examined demographic, socioeconomic, and cultural predictors of resilience. RESULTS: Participants included 448 children (236 PHIV, 98 PHEU, 114 HUU), with median (interquartile range) age at first evaluation of 7 (6-9) years. Children with PHIV exhibited similar rates of resilience as PHEU and HUU on the Externalizing and Total Problems scales. Resilience on the Internalizing scale was more likely in PHEU (71%) compared with PHIV (59%) or HUU (56%), P = 0.049. Factors associated with resilience in adjusted models included: HIV-exposed but uninfected status, higher household income, Cambodian nationality, female sex, and caregiver type. CONCLUSION: Despite biopsychosocial risks, resilience is observed among PHIV and PHEU children. Further study is needed to understand mechanisms underlying associated factors and intervention priorities.